Prologue - Lancaster, Wayne D. (2015)
Thirty years ago it was recognized that nuclear and cytoplasmic changes in exfoliated cervical cells (koilocytes) were pathognomonic for infection by the human papillomavirus (HPV). The observation that HPV cytology detected preneoplastic changes and infection (which led to the reduction of cancer incidence in industrialized countries), led to the hypothesis that the virus would be involved in the etiology of cervical cancer. Subsequent identification of HPV antigens in cells coilocitóticas coexisting with dysplasias, added strength to this hypothesis. The cloning of HPV genomes in cells from genital lesions provided enough weapons that were used in retrospective and prospective studies of the natural history of cervical cancer and its precursors.